(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Description of the knowledge, attitudes, and practices of COVID-19 prevention of students at Tay Ninh Medical College, 2023. Methods: A descriptive cross-sectional design was conducted on 326 students at Tay Ninh Medical College from May 2023 to November 2023. Results: The percentage of students with correct knowledge about COVID-19 disease prevention was 84.4%, positive attitude about COVID-19 disease prevention was 76.1%, and correct practice about COVID-19 disease prevention was 83.1%. The percentage of students with correct knowledge about the minimum time for washing hands for at least 30 seconds was not high at 71.5%. The percentage of students practicing correctly was less than 85%: Washing hands before wearing a mask and after removing the mask was 79.8%, and washing hands for at least 30 seconds each time was 81.6%. Conclusion: It is necessary to educate and improve COVID-19 prevention practices for students.